Physico-chemical evaluation of cupuaçu pulp, Theobroma grandiflorum Schum, handmade and industrial - Silva-Júnior, Antonio Carlos; Freitas do Nascimento, Jaqueline; do Socorro Leôncio Tostes, Ediluci; do Socorro Santos da Silva, Anne (Pubvet, 2019)
The pulp of the fruit is its most commercially important part, and can be produced during the harvest, later stored and processed in periods where there is less fruit production. The cupuaçu, Theobroma grandiflorum Schum, can be considered one of the most important fruits of the region, having excellent market acceptance. For this reason, the objective of the work was to perform the physicochemical characterization of cupuaçu pulps produced artisanal and industrially and commercialized in the city of Macapá-Brazil. Three pulps were produced, handcrafted and marketed at a public fair and three commercially produced pulps sold in a supermarket in the city of Macapá. Both were transported in isothermal boxes to the Laboratory of Physical-Chemical Analysis belonging to the Nucleus of Science and Technology of Food of the Institute of Scientific and Technological Research of the State of Amapá – IEPA. Physicochemical analyzes of pH, total soluble solids (TSS), titratable total acidity (ATT), moisture, protein, lipids, fibers and ascorbic acids (Vitamin C) were carried out, all in triplicates. The protein value found in this study was 2.59 ± 0.8 for industrial pulps and 2.72 ± 0.3 for handmade pulps. The moisture content was 86.73 ± 0.4 for industrial pulps and 97.33 ± 1.3. The pH found in this study was very acidic, with no significant differences, with values of 3.34 ± 0.7 for industrial pulps and 3.67 ± 0.1 for handmade pulps. As for the soluble solids, the values found in the study were for industrial and artisanal pulps, respectively, of 11.67 ± 1.9 ° Brix and 7.67 ± 3.7 ° Brix. Only the artisanal pulps were outside the determined standard that advocates the value of 9° Brix. The differences found in fruit pulps may be of fruit origin (such as maturation, soil and production system), or handling (storage, processing, packaging and transport), these characteristics and processes result in variations described in this paper.